Web-based Self-Reflection Assessment for EFL Students Self-Development - Mandalika, Dewinta; Sulistyaningrum, Siti Drivoka (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Web-based self-reflection assessments are tools to reflect on learning experiences and monitor personal development. It helps to identify strengths and weaknesses in learning process, set goals for improvement, and track progress over time. This study focuses on the use of self-reflection assessment in English language learning, as well as numerous benefits that students can obtained. A systematic review was employed in this study to investigate the potential of web-based self-reflection assessment for EFL students self-development by analyzing publication from Google Scholar & ERIC using specific keywords related to the research topic. The search criteria included studies published in English between 2021 to 2022. In total, 10 relevant selected articles, Preferred Reporting Items for Systematic review, and Meta-Analyses (PRISMA) 2020 guidelines were utilized. An inclusion and exclusion criteria selection process was conveyed prior to the start of the review to assure the focus of the study. Based on the findings, the articles reviewed claimed that self-reflection assessment can help to improve students' language skills, enhancing engagement, boosting confidence, promoting critical thinking, facilitating meaningful learning, reflect on performance & learn from mistakes, motivating individual learning and development, and develop strategies to reach good learning goals. The study concludes that the tool is a useful resource for EFL students seeking to enhance their personal growth and could potentially benefit other institutions looking to integrate self-reflection assessment into their programs. The tool's accessibility and immediate feedback, make it a powerful tool for promoting personal growth and academic success. Keywords: web-based, self-reflection, EFL students, self-development.